Multiplex Assays for Analysis of Antibody Responses to South Asian Plasmodium falciparum and Plasmodium vivax Malaria Infections - Elizabeth O. Momoh; Sonam K. Ghag; John White; Devaraja G. Mudeppa; Pradipsinh K. Rathod (Vaccines, 2023)
Malaria remains a major global health challenge, causing over 0.6 million yearly deaths. To understand naturally acquired immunity in adult human populations in malaria-prevalent regions, improved serological tools are needed, particularly where multiple malaria parasite species co-exist. Slide-based and bead-based multiplex approaches can help characterize antibodies in malaria patients from endemic regions, but these require pure, well-defined antigens. To efficiently bypass purification steps, codon-optimized malaria antigen genes with N-terminal FLAG-tag and C-terminal Ctag sequences were expressed in a wheat germ cell-free system and adsorbed on functionalized BioPlex beads. In a pilot study, 15 P. falciparum antigens, 8 P. vivax antigens, and a negative control (GFP) were adsorbed individually on functionalized bead types through their Ctag. To validate the multiplexing powers of this platform, 10 P. falciparum-infected patient sera from a US NIH MESA-ICEMR study site in Goa, India, were tested against all 23 parasite antigens. Serial dilution of patient sera revealed variations in potency and breadth of antibodies to various parasite antigens. Individual patients revealed informative variations in immunity to P. falciparum versus P. vivax. This multiplex approach to malaria serology captures varying immunity to different human malaria parasite species and different parasite antigens. This approach can be scaled to track the dynamics of antibody production during one or more human malaria infections.